Motion behavior of droplets on curved leaf surfaces driven by airflow - Gao, Zhou-Ming; Hu, Wei; Dong, Xiao-Ya; Zhao, Xiao-Yuan; Wang, Song; Chen, Jian; Qiu, Bai-Jing (Frontiers in Plant Science, 2024)
In air-assisted spraying, pesticide droplet retention on crop leaves is key to evaluating spray effectiveness. However, airflow can deform leaves, reducing droplet retention and affecting spray performance. This study used wind tunnels and high-speed cameras to capture leaf deformation at different airflow speeds and the motion of droplets on curved leaf surfaces. The results showed that leaf curvature during bending deformation is generally less than 0.05 mm-1. Critical wind speed for droplet movement is negatively correlated with droplet size and leaf curvature, with a 24.8% difference between different leaf curvatures and a 17.5% difference between droplet sizes. The droplet’s dimensionless shape variable is positively correlated with both droplet size and leaf curvature. The maximum shape variable on curved leaves reaches 0.24, with acceleration differences of about 30%, while droplets of different sizes show a maximum shape variable of 0.18 and an acceleration difference of up to 68%. These findings enhance understanding of droplet-leaf interactions and provide insights for improving pesticide efficiency.